Expression of Cathepsins B, D, and G in Hypertrophic Port-wine Stain. Issue 3 (27th August 2021) - Koh, Sabrina P.; Brasch, Helen D.; Patel, Josie; Bockett, Nicholas; Paterson, Erin; Davis, Paul F.; Tan, Swee T.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Cathepsins B, D, and G are expressed in vascular anomalies, fibroproliferative conditions, and malignancies. We investigated expression of these cathepsins and their localization to the embryonic stem cell (ESC)-like population in hypertrophic port-wine stain (hPWS). Methods: Immunohistochemical staining for cathepsins B, D, and G was performed on 15 hPWS tissue samples. Immunofluorescence dual staining investigated localization of the cathepsins with endothelial marker CD31, ESC markers OCT4 and SOX2, and mast cell markers chymase and tryptase on 2 hPWS tissue samples. Protein and transcript expression were investigated by western blotting and reverse-transcription quantitative polymerase chain reaction on 6 tissue samples and 3 hPWS-derived primary cell lines, respectively. Enzymatic activity assays of cathepsins B and D were performed on 6 tissue samples. Results: Immunohistochemical staining demonstrated expression of cathepsins B and D on the endothelium and media of lesional vessels and cells within the stroma. Cathepsin G was expressed in the stroma. Immunofluorescence staining showed localization of cathepsins B and D to the OCT4+/SOX2+ population, and cathepsin G to mast cells, in hPWS. Reverse-transcription quantitative polymerase chain reaction demonstrated transcript expression of all 3 cathepsins in hPWS tissues and cathepsins B and D in cell lines. Protein expression and enzymatic activity of cathepsins B and D was confirmed by western blotting and enzymatic activity assays, respectively. Conclusion: Cathepsins B and D are expressed by the ESC-like population on the endothelium and media of the lesional vessels and stroma, and cathepsin G is expressed by mast cells in hPWS. Functional investigations are needed to fully elucidate the functional role of these cathepsins in hPWS.